Synthesis of highly crosslinked monodisperse polymer particles: Effect of reaction parameters on the size and size distribution - Choi, J; Kwak, SY; Kang, S; Lee, SS; Park, M; Lim, S; Kim, J; Choe, CR; Hong, SI (JOHN WILEY & SONS INC, 2002)
Monodisperse polystyrene particles crosslinked with different concentrations of divinylbenzene were synthesized in the 3.2-9.1 mum size range by dispersion polymerization in an isopropyl alcohol/toluene mixed-dispersion medium with poly(N-vinylpyrrolidone) as a steric stabilizer and 2,2'-azobisisobutyronitrile as a radical initiator. The effects of the reaction parameters such as the crosslinking agent concentration, media solvency (controlled by varying the amount of toluene addition), the initiator concentration, and the stabilizer concentration on the particle size and size distribution were investigated with reference particles with a monodisperse size distribution and crosslinked by 1.5 wt % divinylbenzene. The appropriate increase in media solvency was a prerequisite for preparing crosslinked particles without coagulated and/or odd-shaped particles. The investigation of the effects of the polymerization parameters also shows that only specific sets of conditions produce particles with a monodisperse size distribution. The glass-transition temperatures of the particles increased with increasing divinylbenzene concentration. (C) 2002 Wiley Periodicals, Inc.
Keywords: DISPERSION POLYMERIZATION; PRECIPITATION POLYMERIZATION; POLAR-SOLVENTS; POLY(DIVINYLBENZENE) MICROSPHERES; POLYSTYRENE PARTICLES; MOLECULAR-WEIGHT; STYRENE; SUSPENSION; DIVINYLBENZENE; MORPHOLOGY